Changes in Antioxidant Enzymes Activity and Metabolomic Profiles in the Guts of Honey Bee (Apis mellifera) Larvae Infected with Ascosphaera apis - Zhiguo Li; Mengshang Hou; Yuanmei Qiu; Bian Zhao; Hongyi Nie; Songkun Su (Insects, 2020)
The fungus Ascosphaera apis, an obligate fungal pathogen of honey bee brood, causes chalkbrood disease in honey bee larvae worldwide. Biological characteristics of the fungal pathogen and the molecular interactions between A. apis and honey bees have been studied extensively. However, little is known about the effects of A. apis infection on antioxidant enzyme activities and metabolic profiles of the gut of honey bee larvae. In this study, sandwich enzyme-linked immunosorbent assay and LC-MS based untargeted metabolomic analysis were employed to determine the changes in the specific activities of antioxidant enzymes and the metabolomic profiles in gut tissues of A. apis-infected larvae (105 A. apis spores per larva) and controls. Results showed that specific activities of superoxide dismutase, catalase and glutathione S-transferase were significantly higher in the guts of the control larvae than in the guts of the A. apis-infected larvae. The metabolomic data revealed that levels of 28 and 52 metabolites were significantly higher and lower, respectively, in the guts of A. apis-infected larvae than in the guts of control larvae. The 5-oxo-ETE level in the infected larvae was two times higher than that in the control larvae. Elevated 5-oxo-ETE levels may act as a potential metabolic biomarker for chalkbrood disease diagnosis, suggesting that A. apis infection induced obvious oxidative stress in the honey bee larvae. The levels of metabolites such as taurine, docosahexaenoic acid, and L-carnitine involved in combating oxidative stress were significantly decreased in the gut of A. apis-infected larvae. Overall, our results suggest that A. apis infection may compromise the ability of infected larvae to cope with oxidative stress, providing new insight into changing patterns of physiological responses to A. apis infection in honey bee larvae by concurrent use of conventional biochemical assays and untargeted metabolomics.